Revisão de Chrysotachina Brauer & Bergenstamm (Diptera, Tachinidae) da América do Sul - Nunez, Enio (2001)
Revision of the Chrysotachina species with occurrence in South America. The species belonging to this genus are easily distinguished from most of the other tachinids by their metallic colour - green, blue or purple, although grey species are known. From the fifteen species cited in the literature for South America, twelve are redescribed: C. aldrichi Nunez et alli, in press; C. braueri Townsend, 1931; C. currani Nunez et alli, in press; C. equatorialis (Townsend, 1912); C. panamensis Curran, 1939; C. peruviana Townsend, 1919; C. purpurea Curran, 1939; C. tieta Nunez et alli, in press; C. townsendi Curran, 1939; C. tropicalis Nunez et alli, in press; C. viridis Nunez et alli, in press; C. willistoni Curran, 1939. The following three species - C. ornata (Townsend, 1927); C. ruficornis (Walker, 1852) and C. tatei Curran, 1939 - are not íncluded in this revision as none material of them was examined. C. ruficornis is cited in the catalogue of GUIMARÃES (1971) as ''unrecognized". The type material of C. peruviana and C. equatorialis was examined. Illustrations of the male terminalia and of two larvae are presented. An identification key for the species from South America is also presented. The geographic distribution of the following species is enlarged: C. braueri for Mexico; C. equatorialis for Argentina; C. panamensis for Ecuador, Peru and Brazil; C. purpurea for Costa Rica and Brazil; C. townsendi for Paraguay and C. willistoni for Costa Rica, Panama, Venezuela, Ecuador and Peru.